EVALUASI PELAKSANAAN DARING DI SMK N 1 CANGKRINGAN PADA MASA PANDEMI COVID 19 - Florensius Jefi; Rabiman Rabiman; Samsul Hadi (Program Studi Pendidikan Vokasional Teknik Mesin, Universitas Sarjanawiyata Tamansiswa, 2022)
The aim of this study was to determine the implementation of e-learning during the Covid 19 pandemic at SMK N 1 Cangkringan. This survey was conducted in March 2021. This study uses an evaluative study design with a qualitative descriptive approach. The valuation model uses the CIPP valuation model (context, input, process, and product). Method of data collection through interviews and documents. The validity of the data using the original triangle. Data analysis techniques include data collection, data reduction, data visualization, and conclusions. The results of the analysis are as follows. (1) The online training activities went smoothly as planned. Online learning is done using computer software. (2) Online learning activities are carried out using Wi-Fi, cell phones, computers, WhatsApp, Google Classroom, videos, PowerPoint, and media for efficient and smooth practice. The school provides 3M devices for online learning. (3) Practical learning will be done alternately for each class according to the timetable set by the teacher, and theoretical support will be done online through Google Classroom. (4) Barriers to learning practice are student activities, unstable signal, internet sharing and lack of parental cooperation in online learning activities. (5) Evaluate e-learning at school monthly, discuss results in regular meeting activities, assess student responses and report results online.